LINGKUNGAN HIDUP STRATEGIS TERHADAP PERENCANAAN TATA RUANG KABUPATEN BOLAANG MONGONDOW TAHUN 2011-2030 - Lepa, Alex A.; Polii, Bobby J.V.; Husain, Jailani (Universitas Sam Ratulangi, 2011)
ABSTRACT Strategic Environmental Assessment (SEA) can be done to ensure that the preparation of policy, planning and program (PPP) on spatial plan draft of Bolaang Mongondow Regency have included the sustainable development. The purpose of this study was (1) to asses whether the PPP have included the linkage, balance, and fairness principles. (2) to identify the environmental impact caused by implementing PPP defined in the Bolmong’s spatial plan. (3) to find out measures in mitigating negative impacts resulting from PPP. The study was performed using quick appraisal approach by means of matrix analysis, expert judgements, secondary data, field survey, and literature. The result revealed that the score of PPP regarding linkage principle was very good (84.24%) as well as balance principle good (79.59%). The fairness principle and SEA principle were very good as well which were (83.72%), (82.52%) respectively. Identified nine issues of sustainable development resulted negative and positive impact . This study implied that mitigating negative impacts could be achieved by integrating SEA principles to articles that not fully considering SEA.